2015
DOI: 10.1007/s10914-015-9304-y
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight and Relative Brain Size (Encephalization) in Eocene Archaeoceti (Cetacea)

Abstract: Calibration of the Brownian diffusion model of Felsenstein indicates that phylogeny may have an influence on body length and other phenotypic measures in Cetacea for as many as 10,000 generations or about 180,000 years, which is negligible in the 35 million year history of extant Cetacea. Observations of phenotypic traits in cetacean species living today are independent of phylogeny and independent statistically. Four methods for estimating body weight in fossil cetaceans are compared: (1) median serial regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
4
31
2
Order By: Relevance
“…In evolutionary history, the animals with the largest brains relative to body mass, the Delphinidae, have experienced a large decrease in body mass [Montgomery et al, 2013]. Studies such as Marino et al [2004] and Montgomery et al [2013] relied heavily on EQ derived from endocranial volume [also see Gingerich, 2015]. Given the vast differences in nonbrain endocranial tissue, we are skeptical of these results.…”
Section: Total Brain Size Differences Relative To Body Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In evolutionary history, the animals with the largest brains relative to body mass, the Delphinidae, have experienced a large decrease in body mass [Montgomery et al, 2013]. Studies such as Marino et al [2004] and Montgomery et al [2013] relied heavily on EQ derived from endocranial volume [also see Gingerich, 2015]. Given the vast differences in nonbrain endocranial tissue, we are skeptical of these results.…”
Section: Total Brain Size Differences Relative To Body Sizementioning
confidence: 99%
“…The smallest adult La Plata dolphin, Pontoporia blainvillei , may weigh as little as 15-20 kg [Kamiya and Yamasaki, 1974;Pirlot and Kamiya, 1975] while the largest blue whale, Balaenoptera musculus , may approach 200,000 kg [Lockyer, 1976]. It is obvious from many studies that brain size does not vary strictly with body size [Pilleri and Gihr, 1970;Pirlot and Kamiya, 1975;Miyazaki et al, 1981;Ridgway and Brownson, 1984;Worthy and Hickie, 1986;Marino et al, 2004;Turner et al, 2006;Connor, 2007;Montgomery et al, 2013;Gingerich, 2015;Mallette et al, 2016]. Data on brains of cetaceans of known maturity have been sparse.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study inferred that the most recent common ancestor of all extant cetaceans was 167 kg [35], whereas another suggested that this taxon was about 2.5 m in length [34]. Using equations that relate body mass to length [37], a cetacean this long should be about 175 kg. Coronodon is much larger: an equation that estimates body length from width across the zygomatic process results in a length of 4.9 m [34].…”
Section: Discussionmentioning
confidence: 99%
“…Coronodon is much larger: an equation that estimates body length from width across the zygomatic process results in a length of 4.9 m [34]. This length corresponds to a mass of 1,150 kg, very similar to the mass estimated for the archaeocete Dorudon atrox [37]. Determining whether Coronodon simply retained the body size of archaeocetes or represents a dramatic increase over a small ancestral neocete will be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation